Molecular fingerprinting by multi-locus sequence typing identifies microevolution and nosocomial transmission of Candida glabrata in Kuwait - Asadzadeh, Mohammad; Ahmad, Suhail; Al-Sweih, Noura; Khan, Ziauddin (Frontiers in Public Health, 2023)
Backgrounds Candida glabrata is a frequently isolated non-albicans Candida species and invasive C. glabrata infections in older patients are associated with high mortality rates. Opportunistic Candida infections in critically ill patients may be either endogenous or nosocomial in origin and this distinction is critical for effective intervention strategies. This study performed multi-locus sequence typing (MLST) to study genotypic relatedness among clinical C. glabrata isolates in Kuwait. Methods Candida glabrata isolates (n = 91) cultured from 91 patients were analyzed by MLST. Repeat isolates (n = 16) from 9 patients were also used. Antifungal susceptibility testing for fluconazole, voriconazole, caspofungin and amphotericin B (AMB) was determined by Etest. Genetic relatedness was determined by constructing phylogenetic tree and minimum spanning tree by using BioNumerics software. Results Resistance to fluconazole, voriconazole and AMB was detected in 7, 2 and 10 C. glabrata isolates, respectively. MLST identified 28 sequence types (STs), including 12 new STs. ST46 (n = 33), ST3 (n = 8), ST7 (n = 6) and ST55 (n = 6) were prevalent in ≥4 hospitals. Repeat isolates obtained from same or different site yielded identical ST. No association of ST46 with source of isolation or resistance to antifungals was apparent. Microevolution and cross-transmission of infection was indicated in two hospitals that yielded majority (57 of 91, 67%) of C. glabrata. Conclusion Our data suggest that C. glabrata undergoes microevolution in hospital environment and can be nosocomially transmitted to other susceptible patients. Thus, proper infection control practices during routine procedures on C. glabrata-infected patients may prevent transmission of this pathogen to other hospitalized patients.